Creating new guidelines on how best to treat foot symptoms in people with EB. (1st March 2020) - Khan, M.T.; O'Sullivan, M.; Faitli, B.; Mellerio, J.E.; Fawkes, R.; Wood, M.; Hubbard, L.D.; Harris, A.G.; Iacobaccio, L.; Vlahovic, T.; James, L.; Brains, L.; et al.
Summary: Epidermolysis bullosa (EB) is a complex rare condition that affects the skin and many parts of the body. Those born with EB have skin so fragile they are called 'butterfly children', their skin is quite simply as fragile as the wing of a butterfly. In the UK it is estimated that there are more than 5, 000 people living with EB and 500, 000 worldwide. Little clinical guidance for care existed until DEBRA International started a programme to develop clinical practice guidelines (CPGs). There were no previous guidelines and few published studies on foot care in EB so treatment decisions were largely based on individual opinion and experience. The panel – made up of clinical experts and people living with EB representing Australia, the UK, and the USA – aimed to describe foot problems in people of all ages with EB, and summarise current evidence and management. The authors used a logical podiatric (foot) care literature review focussed on patients with EB. The authors found that the evidence in this area was limited but several interventions (treatments) currently practised by podiatrists show positive outcomes. The study allowed the group to make recommendations on how to treat foot and nail disorders in patients with EB. Furthermore, the authors concluded that further research is needed. This is a summary of the study: Foot care in epidermolysis bullosa: evidence‐based guideline